Comparative Analysis of T-Cell Responses to Aquaporin-4 and Myelin Oligodendrocyte Glycoprotein in Inflammatory Demyelinating Central Nervous System Diseases - Hofer, Livia Sophie; Ramberger, Melanie; Gredler, Viktoria; Pescoller, Anna Sophie; Rostásy, Kevin; Sospedra, Mireia; Hegen, Harald; Berger, Thomas; Lutterotti, Andreas; Reindl, Markus (Frontiers in Immunology, 2020)
Autoantibodies against aquaporin-4 (AQP4-Ab) and myelin oligodendrocyte glycoprotein (MOG-Ab) are associated with rare central nervous system inflammatory demyelinating diseases like neuromyelitis optica spectrum disorders (NMOSD). Previous studies have shown that not only antibodies, but also autoreactive T-cell responses against AQP4 are present in NMOSD. However, no study has yet analyzed the presence of MOG reactive T-cells in patients with MOG antibodies. Therefore, we compared AQP4 and MOG specific peripheral T-cell response in individuals with AQP4-Ab (n=8), MOG-Ab (n=10), multiple sclerosis (MS, n=8) and healthy controls (HC, n=14). Peripheral blood mononuclear cell cultures were stimulated with eight AQP4 and nine MOG peptides selected from previous studies and a tetanus toxoid peptide mix as a positive control. Antigen-specific T-cell responses were assessed using the carboxyfluorescein diacetate succinimidyl ester proliferation assay and the detection of granulocyte macrophage colony-stimulating factor (GM-CSF), interferon (IFN)-ɣ and interleukin (IL)-4, IL-6 and IL-17A in cell culture supernatants. Additionally, human leukocyte antigen (HLA)-DQ and HLA-DR genotyping of all participants was performed. We classified a T-cell response as positive if proliferation (measured by a cell division index ≥3) was confirmed by the secretion of at least one cytokine. Reactivity against AQP4 peptides was observed in many groups, but the T-cell response against AQP4 p156-170 was present only in patients with AQP4-Ab (4/8, 50%) and absent in patients with MOG-Ab, MS and HC (corrected p=0.02). This AQP4 p156-170 peptide specific T-cell response was significantly increased in participants with AQP4-Ab compared to those without (Odds ratio-OR 59.00, 95% confidence interval-CI 2.70 to 1290.86). Moreover, T-cell responses against at least one AQP4 peptide were also more frequent in participants with AQP4-Ab (OR=11.45, 95% CI 1.24 to 106.05). We did not observe any significant differences for the other AQP4 peptides or any MOG peptide. AQP4-Ab were associated with HLA DQB1*02 (OR=5.71, 95% CI 1.09 to 30.07), DRB1*01 (OR=9.33, 95% CI 1.50 to 58.02) and DRB1*03 (OR=6.75, 1.19 to 38.41). Furthermore, HLA DRB1*01 was also associated with the presence of AQP4 156-170 reactive T-cells (OR=31.67, 95% CI 1.30 to 772.98). To summarize, our findings suggest a role of AQP4-specific, but not MOG-specific T-cells, in NMOSD.